Liturgical Modifications in the Early Byzantine Church in Eretz Israel. The Architectural and Epigraphic Evidence - Ovadiah, A. (Liber Annuus, 2005)
Abstract Liturgical modifications, followed by architectural modifications in the church complex, did indeed take place in Eretz Israel in the early Byzantine period, but for the time being there is no evidence to indicate that these modifications were the direct result of a religious-ecclesiastical decree, binding for all churches. Therefore, it can be assumed that the discussed modifications were specific to a particular church or to the churches of a particular settlement, for which the circumstances demanded their implementation. Precisely when these modifications took place, whether during the sixth century, the second half of that century, and up to the beginning of the seventh century CE, cannot be determined.